Proceedings of the 2014 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2014
DOI: 10.1145/2632048.2632060
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale evaluation of call-availability prediction

Abstract: We contribute evidence to which extent sensor-and contextual information available on mobile phones allow to predict whether a user would pick up a call or not. Using an app publicly available for Android phones, we logged anonymous data from 31311 calls of 418 different users. The data shows that information easily available in mobile phones, such as the time since the last call, the time since the last ringer mode change, or the device posture, can predict call availability with an accuracy of 83.2% (Kappa =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…27) suggesting to open a piece of content from Buzzfeed. Our participants were predicted to be bored by our algorithm in 48.0% of the cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27) suggesting to open a piece of content from Buzzfeed. Our participants were predicted to be bored by our algorithm in 48.0% of the cases.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it has been shown that computing devices are able to detect a person's openness to receiving office visits [16], emails [21], messages from desktop instant messengers [1], SMS and mobile phone messages [30], mobile phone alerts [31], and mobile phone calls [20,27].…”
Section: Inferring Emotions From Mobile Phone Usagementioning
confidence: 99%
See 1 more Smart Citation
“…Proposals for automatically inferring a persons availability in office spaces [15] and desktop instant messengers [2], phone calls [25] and mobile instant messengers [26] have been explored. Other researchers have investigated the use of rich-presence information including motion, location and music to enable users to determine when and how to contact an individual in mobile environments [4].…”
Section: Communicating Availabilitymentioning
confidence: 99%
“…However, these techniques do not take into account the freshness of rules, i.e., rules that represent recent patterns, in which we are interested to output a complete set of updated behavioral rules based on recency for individual mobile phone users utilizing their contextual smartphone datasets. In order to mine users' contextual mobile phone data to model their behavior, a number of authors use a static period of phone log data, such as phone call logs [22][23][24][25], SMS Log [26], mobile application (apps) usages logs [3,27,28], mobile phone notification logs [10], web logs [29][30][31], game Log [32], context logs [4], and smartphone life log [33,34] etc. for various purposes.…”
Section: Background and Related Workmentioning
confidence: 99%